Helicobacter pylori seroprevalence in Spain: influence of adult and childhood sociodemographic factors. Issue 4 (July 2019) - Lorenzo, Irene; Fernández-de-Larrea, Nerea; Michel, Angelika; Romero, Beatriz; Lope, Virginia; Bessa, Xavier; Moreno, Victor; Martín, Vicente; Amiano, Pilar; Castilla, Jesús; Tardón, Adonina; Dierssen-Sotos, Trinidad; et al.
Abstract : Helicobacter pylori ( H. pylori ) chronic infection causes severe digestive diseases, including gastric cancer, and certain strains entail a higher risk. Risk factors for this infection are still not fully understood. The aim of this study was to describe the association of adult and childhood sociodemographic factors with the seroprevalence of H. pylori, and with CagA and VacA antigen-specific seropositivity among H. pylori -seropositive individuals in the Spanish adult population. Serum antibody reactivity to H. pylori proteins was evaluated using multiplex serology in 2555 population-based controls enrolled in the MCC-Spain study, a multicase–control study recruiting participants from 2008 to 2013 in different areas of Spain. H. pylori seroprevalence was defined as seropositivity against at least four bacterial proteins. Information on sociodemographics, lifestyles, and environmental exposures was collected through personal interviews. Prevalence ratios and 95% confidence intervals were estimated using Poisson regression models to assess the association of lifetime sociodemographic factors with H. pylori seroprevalence and with seropositivity for CagA and VacA. H. pylori seroprevalence was 87.2%. Seropositivity was statistically significantly higher in men, increased with age, BMI, and number of siblings, and decreased with education and socioeconomic family level at birth. Among H. pylori -seropositive individuals, seropositivity was 53.3% for CagA, 61.4% for VacA, and 38.8% for both CagA and VacA. Ever smokers had lower seroprevalence for CagA and VacA than never smokers. H. pylori seroprevalence among this Spanish adult population was high and one third of the population was seropositive for two well-known markers of gastric cancer risk: CagA and VacA. Sex, age, education, and BMI were associated with H. pylori seroprevalence. Abstract : Supplemental Digital Content is available in the text.